Ocalić tajemnicę - specyfika inscenizacyjna teatru tańca Piny Bausch - Roszak, Monika (Wydawnictwo Naukowe UAM, 2009)
In the article are presented the fundamental determinants of the style of the theatre of Pina Bausch. Tanztheater Wuppertal performances delight with their totality and originality (stage design, costumes, the musical layer, textual layer). Montage, collage, acting based on improvisation - these are the means which are the pillars of Bausch's theatre. Tanztheater Wuppertal performances have reformed the modern ballet and created a new kind of performance based - apart from dance, movement and pantomime - on the realistic activities, routine behaviours, dialogues and singing
Save the mystery - staging specificity of Pina Bausch's dance theatre